Enhancement in Thermoelectric Power in Lead Telluride Nanocomposite: Role of Oxygen Vis-À-Vis Nanostruct - B. Paul; P. Banerji (Журнал нано- та електронної фізики)
The present work reports enhanced power factor and reduced value of room temperature thermal conductivity in undoped PbTe nanocomposite, prepared from PbTe nanocrystals, synthesized via chemical route. The highest power factor is found to be 19.21 x 10 –4 Wm –1K –2 with room temperature thermal conductivity of 1.53 Wm –1K –1. The potential barrier at the sharp interfaces of the grains of the nanocomposites, occurred due to the adsorption of oxygen by the grain surfaces, have been found to play the main role to produce the high value of Seebeck coefficient (416 μV/K at 500 K) by preferentially scattering the lower energy electrons and thus enhancing the power factor. The lattice destruction at the grain interfaces has been found to cause the remarkable reduction in thermal conductivity, through scattering a wide spectrum of phonon wavelength.